GAMBARAN ACTIVE PROCRASTINATION PADA MAHASISWA YANG SEDANG MENGERJAKAN SKRIPSI - Elsa Gabriella; Ferdian, Flaviana Rinta (MANASA, 2024)
Completing a thesis is a key requirement for undergraduate students, but the process often presents various challenges. In response, some students engage in maladaptive behaviors such as procrastination. While traditionally viewed as detrimental, recent studies have identified a positive form of procrastination called active procrastination. This involves intentionally delaying tasks, feeling motivated under time pressure, meeting deadlines, and achieving satisfactory results. Active procrastination can serve as a productive strategy with potential benefits for undergraduates. This study explored the prevalence and levels of active procrastination among thesis-writing undergraduates. Data were collected from 298 students across universities in Indonesia using convenience sampling. The Active Procrastination Scale-Bahasa Indonesia by Purwanto and Natalya (2019) was employed to measure active procrastination. Findings revealed that thesis students generally exhibit low levels of active procrastination. Additionally, no significant gender differences were observed. The study also found significant correlations among the dimensions of active procrastination. These results suggest that promoting active procrastination may help students adopt a more adaptive approach to managing thesis-related challenges.